The Female Experience of the Other - Owczarek, Dorota (Studia Anglica Posnaniensia, 2016)
The following paper deals with the problem of the transformation of the female self from the ethnocentric stage to the ethnorelative stage, as portrayed in Osa Johnson’s “autobiographical” account of her trips in the book I married adventure. The author attempts to show the metamorphosis of the protagonist by relating her experiences to the developmental model of cultural sensitivity, as proposed by M.J. Bennett. It is argued that the protagonist assumes the role of the Other in relation to her husband in the same way that indigenous people appear as the Other in relation to the protagonist. The slight yet detectable change in her perception of the Other constitutes an attempt to liberate herself from the position of the subordinate white female.